Discussion of an Empirical Study of Error Characteristics in Audit Populations - Festge, Michael O. (Journal of Accounting Research, 1979)
Michael O. Festge, Discussion of an Empirical Study of Error Characteristics in Audit Populations, Journal of Accounting Research, Vol. 17, Studies on Auditing-Selections from the "Research Opportunities in Auditing" Program (1979), pp. 103-107